Mortality after total colectomy in 3084 patients with inflammatory bowel disease: a population‐based cohort study. Issue 3 (18th June 2014) - Nordenvall, C.; Ekbom, A.; Bottai, M.; Smedby, K. E.; Nilsson, P. J.
Summary Background A high post‐operative mortality has been reported following colectomy in patients with inflammatory bowel disease (IBD), especially in some patient groups. Aims To investigate the 40‐day mortality following colectomy in patients with IBD. The secondary aim was to assess whether colectomised IBD patients have an increased mortality compared to the general population. Methods This is a population‐based register study of all patients with IBD in Sweden who underwent total colectomy in 2000–2010. The cohort was identified using international classification codes for ulcerative colitis (UC) and Crohn's disease (CD). Patients registered with both UC and CD before colectomy (UCCD) were analysed separately. Each patient was followed‐up to the date of death, migration or 31st of December 2010, whichever came first. Kaplan–Meier survival curves, Cox proportional hazards models and relative mortality rates were used to describe mortality. Results In the cohort of 3084 patients, 2424 were diagnosed with UC, 326 with CD and 334 with UCCD. The 40‐day, 1‐year and 3‐year mortality was 1.3%, 3.1% and 6.0%, respectively. The highest 40‐day mortality was seen in patients ≥59 years of age (4.4%). Colectomy at the primary hospitalisation for IBD did not significantly increase the risk of post‐operative mortality, nor did hospital volume. The relative survival after 3 years was 0.99, 0.98, 0.97 and 0.90 in those <30, 30–43, 44–58 and ≥59 years old, respectively. Conclusion The 40‐day mortality following total colectomy in IBD patients in Sweden is low, except in patients ≥59 years old.